2011
DOI: 10.1007/s10750-011-0828-8
|View full text |Cite
|
Sign up to set email alerts
|

Biotelemetry of crustacean decapods: sampling design, statistical analysis, and interpretation of data

Abstract: The implementation of ultrasonic telemetry as a technique to evaluate ecological traits of marine organisms has allowed biologists to obtain information that is hard or impossible to achieve by traditional sampling methods; which in turn improves the quantification, in their natural habitats, of activity patterns, movements, migrations, habitat utilization and zonation, among other biological and physiological variables. Despite its transcendence, this technique has been scantly applied in crustacean decapod s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…However, use of telemetry on crustaceans has lagged behind its use on other taxa (e.g. fish: Guerra-Castro et al 2011, Abecasis et al 2018, and as such, there are a limited number of studies with information on individual-level movements of crustaceans (Holyoak et al 2008). The utility of telemetry is species-, system-, and question-specific.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, use of telemetry on crustaceans has lagged behind its use on other taxa (e.g. fish: Guerra-Castro et al 2011, Abecasis et al 2018, and as such, there are a limited number of studies with information on individual-level movements of crustaceans (Holyoak et al 2008). The utility of telemetry is species-, system-, and question-specific.…”
Section: Introductionmentioning
confidence: 99%
“…These reviews documented trends in taxa-specific and geographic foci, identified limitations of the technology, and provided suggestions for future research and areas that were understudied. Guerra-Castro et al (2011) reviewed the use of telemetry on decapods, but focused on statistical analyses of telemetry data. Therefore, an opportunity exists to update the status of telemetry use on decapods globally to highlight knowledge gaps and guide future research.…”
Section: Introductionmentioning
confidence: 99%
“…AT reduces the re liance upon baitedtraps, which are constrained by issues of variable effort, catchability and trap saturation; these issues have historically hindered the robustness of findings. Despite the obvious advantages, AT has not yet been applied to crustaceans in the UK (Guerra-Castro et al 2011), where movement and space-utilisation remain poorly investigated (but see Smith et al 1998Smith et al , 2001. AT and data storage tags have been applied to H. gammarus on 3 occasions in Norway (van der Meeren 1997, Moland et al 2011a, Wiig et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Guerra‐Castro et al . () acoustic telemetry offers several advantages over mark–recapture studies, as frequent position estimates of tagged individuals can be obtained without disturbing the animals and data are independent of fishing effort.…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing techniques such as acoustic telemetry have been applied in recent years to different lobster species such as Homarus americanus, Panulirus argus, Panulirus cygnus, Jasus lalandii (Atkinson et al 2005;MacArthur et al 2008;Bertelsen & Hornbeck 2009;Scopel et al 2009). As reviewed by Guerra-Castro et al (2011) acoustic telemetry offers several advantages over mark-recapture studies, as frequent position estimates of tagged individuals can be obtained without disturbing the animals and data are independent of fishing effort.…”
Section: Introductionmentioning
confidence: 99%